2020
DOI: 10.1101/2020.05.18.101899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downregulation of E-cadherin in pluripotent stem cells triggers partial EMT

Abstract: Epithelial to mesenchymal transition (EMT) is a critical cellular process that has been well characterized during embryonic development and cancer metastasis and it also is implicated in several physiological and pathological events including embryonic stem cell differentiation. During early stages of differentiation, human embryonic stem cells pass through EMT where deeper morphological, molecular and biochemical changes occur. Though initially considered as a decision between two states, EMT process is now r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…This concordance suggests an overlap of core expression patterns central to EMT in a highdimensional feature space and indicates that these metrics -initially developed for cancer samples -can be applied more generally to a broader range of biological contexts. Using these metrics in biological contexts where hybrid E/M states have been proposed (Aban et al, 2020;Grande et al, 2015;Jolly et al, 2018) may be helpful in mapping the corresponding trajectories of EMT/MET. The hybrid E/M state has been previously documented at both bulk and single-cell levels during various stages of development as well (Dong et al, 2018;Leroy and Mostov, 2007); here, we have shown proof-of-principle that these scoring metrics can successfully quantify the extent of EMP in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…This concordance suggests an overlap of core expression patterns central to EMT in a highdimensional feature space and indicates that these metrics -initially developed for cancer samples -can be applied more generally to a broader range of biological contexts. Using these metrics in biological contexts where hybrid E/M states have been proposed (Aban et al, 2020;Grande et al, 2015;Jolly et al, 2018) may be helpful in mapping the corresponding trajectories of EMT/MET. The hybrid E/M state has been previously documented at both bulk and single-cell levels during various stages of development as well (Dong et al, 2018;Leroy and Mostov, 2007); here, we have shown proof-of-principle that these scoring metrics can successfully quantify the extent of EMP in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…However, more sophisticated studies have now refuted that idea, and instead support an alternative model wherein most cell fate changes -including both EMT and EndoMT -involve progressive transition from one cell identity to another via a fluid spectrum of intermediate cell states (Lamouille et al, 2014;Sha et al, 2019). In support of this latter model, initiation of EMT in pluripotent epithelial stem cells through downregulation of the adherens junction protein E-cadherin triggers expression of Slug and related transcription factors, leading to the acquisition of some mesenchymal characteristics; yet, these cells still retain expression of epithelial stem cell markers indicating only a partial EMT (Aban et al, 2021).…”
Section: Model Of Partial Endomt Regulationmentioning
confidence: 92%
“…44,45 E-cadherin also plays an important role in maintaining cell adhesion and polarity and when mutated, there is a loss of contact inhibition and cell migration. 46,47 Hereditary nonpolyposis colon cancer syndrome is another autosomal dominant disorder associated with an increased risk of GC. This disease is characterized by a mutation in the DNA repair system (MLH1, MSH2, MSH6, PMS2, etc.)…”
Section: Hereditarymentioning
confidence: 99%
“…When E‐cadherin is mutated, it was found that Wnt signaling regulates both proliferation and chemotherapy resistance in GC 44,45 . E‐cadherin also plays an important role in maintaining cell adhesion and polarity and when mutated, there is a loss of contact inhibition and cell migration 46,47 . Hereditary nonpolyposis colon cancer syndrome is another autosomal dominant disorder associated with an increased risk of GC.…”
Section: Etiology Of Gcmentioning
confidence: 99%